Diseño y simulación de una máquina clasificadora de tomate de riñón para los productores del sector de Pataín perteneciente a la parroquia Panzaleo de la provincia de Cotopaxi. - Espín Bautista, Lenin Mauricio (2020)
The present technological proposal aims to design and simulate a kidney tomato sorting machine, through mathematical analysis and a finite element method, for producers in the Pataín sector belonging to the Panzaleo parish in the Cotopaxi province, analyzing the main variables in the process; using a selection of the type of machine, transmission system, using existing materials in the local market. The kidney tomato sorter is made up of inlet and outlet hoppers, electric motor, catalysts, reinforced rollers, keys, guide shafts and the support structure. Therefore, the machine has the ability to classify the product according to its size, defined in certain cycles, generating movement by the rollers which are driven by link chains, moving the tomato into different modules, dividing the product according to its size. The machine supports the agricultural sector, to automatically classify the product of up to 15 tons per week, working only 3 hours per day, defining the design using CAD CAE tools, which is validated through finite element analysis to show the influence of the machine variables.